Analisis Faktor-Faktor Yang Mempengaruhi Pertumbuhan Ekonomi di Kabupaten Mimika - Verselilna M Berkat; Natalia Lumentah (Journal of Economics and Regional Science, 2022)
This study aims to determine the factors that influence economic growth in Mimika Regency. The research method used is the associative method. In this research, the data collection technique used is literature study and documentation. To determine the factors that influence economic growth in Mimika Regency, the analysis used in this study is multiple linear regression analysis. The results of this study indicate that household consumption, government spending and net exports affect economic growth in Mimika Regency but investment has no effect on economic growth